2014
DOI: 10.3928/00989134-20131028-04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pressure Ulcers by Race and Ethnicity for Older Adults Admitted to Nursing Homes

Abstract: Little is known about the prevalence of pressure ulcers among racial and ethnic groups of older individuals admitted to nursing homes (NHs). NHs admitting higher percentages of minority individuals may face resource challenges for groups presenting with more pressure ulcers or ones of greater severity. This study examined the prevalence of pressure ulcers (Stages 2-4) among older adults admitted to NHs by race and ethnicity at the individual, NH, and regional levels. Results show that the prevalence of pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…A higher prevalence of pressure ulcers among Blacks compared to Whites (from 1% to 4% difference) has been observed in various cross-sections of NH residents (Cai, Mukamel, & Temkin-Greener, 2010; Lapane, Jesdale, & Zierler, 2005; Li, Yin, Cai, Temkin-Greener, & Mukamel, 2011). We are among those who have reported that the incidence of pressure ulcers is also greater among Black NH residents (Baumgarten et al, 2004; Harms et al, 2014; Rosen et al, 2006). The results of this study reveal that Black older adults with a pressure ulcer at NH admission are less likely to heal a pressure ulcer by the 90-day MDS assessment than would be expected had they been part of the White group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A higher prevalence of pressure ulcers among Blacks compared to Whites (from 1% to 4% difference) has been observed in various cross-sections of NH residents (Cai, Mukamel, & Temkin-Greener, 2010; Lapane, Jesdale, & Zierler, 2005; Li, Yin, Cai, Temkin-Greener, & Mukamel, 2011). We are among those who have reported that the incidence of pressure ulcers is also greater among Black NH residents (Baumgarten et al, 2004; Harms et al, 2014; Rosen et al, 2006). The results of this study reveal that Black older adults with a pressure ulcer at NH admission are less likely to heal a pressure ulcer by the 90-day MDS assessment than would be expected had they been part of the White group.…”
Section: Discussionmentioning
confidence: 94%
“…Earlier reports reveal that more Blacks than Whites enter NHs with pressure ulcers and with more severe pressure ulcers (Baumgarten et al, 2004; Harms et al, 2014). A higher prevalence of pressure ulcers among Blacks compared to Whites (from 1% to 4% difference) has been observed in various cross-sections of NH residents (Cai, Mukamel, & Temkin-Greener, 2010; Lapane, Jesdale, & Zierler, 2005; Li, Yin, Cai, Temkin-Greener, & Mukamel, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent trend found across a number of the studies reviewed showed that people with DSTs had the highest risk of higher stages of PI (Ahn, Cowan, Garvan, Lyon, & Stechmiller, ; Baumgarten et al., ; Cai et al., ; Fogerty, Guy, Barbul, Nanney, & Abumrad, ; Gerardo et al. ; Harms et al., ; Li, Yin, Cai, Temkin‐Greener, & Mukamel, ; VanGilder, MacFarlane, & Meyer, ). Findings from one study suggested that people who had skin classified as medium or dark were more likely to develop PIs with a visible break in their skin (VanGilder et al., ).…”
Section: Resultsmentioning
confidence: 67%
“…This statement is reinforced by Harms et al. 's () study where people admitted to nursing homes who had been categorised as Black had a 1.7 higher chance of developing PIs than people categorised as White. Whilst PI risk amongst people with DSTs is high, the stage of PI varied; as drawing on further from Harms et al.…”
Section: Resultsmentioning
confidence: 96%